Optimization of an Activity Assay of Coprinus Cinereus Peroxidase - Dong,Bing Xue (2018)
ABSTRACT To seek a simple, rapid and sensitive Coprinus cinereus Peroxidase (CIP) activity assay, a convenient one-factor-at-a-time (OFAT) method and a response surface methodology (RSM) were used. The recombinant CIP expressed in Pichia pastoris was purified with the Ni-NTA spin column. Based on the results of catalytic efficiency (kcat/Km) analysis, 2,2'-azinobis (ethylbenzthiazoline -6-sulfonate) (ABTS) was selected as the optimal enzyme substrate. Results of the OFAT method showed that enzymatic reaction performed in 0.1 mol/L sodium acetate (pH 5.0) buffer in a 200-µl reaction mixture containing 0.5 mmol/L ABTS, 10 mmol/L hydrogen peroxide (H2O2), 49.7 ng CIP at 25°C gave an average CIP activity of 88 U/mL. The ABTS and H2O2 concentrations were then further optimized to improve the sensitivity of the assay. To do that, RSM was conducted through central composite design, and a reduced quadratic model with good fit regression equation was generated. ANOVA analysis of this model indicated that the concentrations of ABTS and H2O2 and their interaction had significant impact on the assay sensitivity. The optimal reaction mixture was determined to include an initial ABTS concentration of 0.82 mmol/L 49.7 ng CIP and 16.36 mmol/L H2O2, and the activity under this condition was determined to be 138.89 U/mL.